2010
DOI: 10.1186/1756-9966-29-100
|View full text |Cite
|
Sign up to set email alerts
|

TNFRSF1B A1466G genotype is predictive of clinical efficacy after treatment with a definitive 5-fluorouracil/cisplatin-based chemoradiotherapy in Japanese patients with esophageal squamous cell carcinoma

Abstract: BackgroundCurrently definitive 5-fluorouracil (5-FU)/cisplatin (CDDP) -based chemotherapy is recognized as one of the most promising treatments for esophageal cancer. A series of studies performed found genetic polymorphisms and the plasma concentration of 5-FU to be predictive of acute severe toxicities and clinical response. Genetic polymorphisms of tumor necrosis factor (TNF) -α and its surface receptors, TNFRSF1A and TNFRSF1B have been examined in terms of susceptibility to various cancers. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Previous studies have shown that an amino acid substitution (methionine to arginine) is caused by the T to G SNP at TNFRII nt587, and that the amino acid substitution is responsible for its proteolytic cleavage, which produces the soluble form of TNFRII (sTNFR) (Beltinger et al, 1996;Oregon-Romero et al, 2006;Kuwahara et al, 2010). STNFR and mTNFR can compete to combine with TNF, which might affect the biological functions of TNF.…”
Section: Tnfrαnt587mentioning
confidence: 99%
“…Previous studies have shown that an amino acid substitution (methionine to arginine) is caused by the T to G SNP at TNFRII nt587, and that the amino acid substitution is responsible for its proteolytic cleavage, which produces the soluble form of TNFRII (sTNFR) (Beltinger et al, 1996;Oregon-Romero et al, 2006;Kuwahara et al, 2010). STNFR and mTNFR can compete to combine with TNF, which might affect the biological functions of TNF.…”
Section: Tnfrαnt587mentioning
confidence: 99%
“…Des polymorphismes génétiques sont en cours d'identification comme le TNFRSF1B et seraient corrélés avec une meilleure réponse in vitro aux protocoles de chimiothérapie associant de la 5-fluoro-uracile et du cisplatine, ce qui nécessite encore la preuve d'un impact clinique [54].…”
Section: Discussionunclassified
“…Studies have been performed to evaluate the effects of genetic polymorphisms on clinical response, survival or severe acute toxicities during treatment with definitive 5-FU/CDDP-based CRT in Japanese patients with ESCC 23-27. They were conducted with the authorization of the Institutional Review Board (IRB) and followed the Medical Research Council guidelines of Kobe University.…”
Section: Methodsmentioning
confidence: 99%
“…Predicting therapeutic responses is important in definitive CRT prior to the initiation of treatment; we previously reported a significant correlation between clinical response and survival, and showed that the TNFRSF1B 1466A/G (rs1061624) genotype could predict clinical response with definitive 5-FU/cisplatin (CDDP)-based CRT in 46 male Japanese patients with ESCC 23. Although these findings suggest that TNF-α and its receptors may play a critical role in clinical response and survival, to the best of our knowledge, no published study has investigated associations between the polymorphisms of TNF-α and TNFRSF1A genes and the prediction of clinical outcome in ESCC patients treated with definitive CRT.…”
Section: Introductionmentioning
confidence: 99%